A superconducting nanowire-based architecture for neuromorphic computing. Issue 3 (1st September 2022) - Lombo, Andres E; Lares, Jesus; Castellani, Matteo; Chou, Chi-Ning; Lynch, Nancy; Berggren, Karl K
Abstract: Neuromorphic computing would benefit from the utilization of improved customized hardware. However, the translation of neuromorphic algorithms to hardware is not easily accomplished. In particular, building superconducting neuromorphic systems requires expertise in both superconducting physics and theoretical neuroscience, which makes such design particularly challenging. In this work, we aim to bridge this gap by presenting a tool and methodology to translate algorithmic parameters into circuit specifications. We first show the correspondence between theoretical neuroscience models and the dynamics of our circuit topologies. We then apply this tool to solve a linear system and implement Boolean logic gates by creating spiking neural networks with our superconducting nanowire-based hardware.